The LiiNK Project®: Effects of Multiple Recesses and Character Curriculum on Classroom Behaviors and Listening Skills in Grades K–2 Children - Rhea, Deborah J.; Rivchun, Alexander P. (Frontiers in Education, 2018)
Unstructured, outdoor play combined with character development instruction has shown preliminary associations with improved cognitive functioning and classroom behaviors. The purpose of this study was to further evaluate these components of the LiiNK Project (Let’s inspire innovation ’N Kids) when including intervention and comparison school children. The intervention consists of four 15-min recesses, scheduled throughout the day in combination with four 15-min character development lessons taught weekly to improve the elementary classroom learning environment. The second year of this longitudinal study included grades kindergarten through second grade students (N = 405) from two demographically comparable private schools in the southwest region of the United States. One school implemented the intervention, while the other school maintained current protocols. The intervention teachers adhered to the four play breaks at a rate of 92% over the course of the intervention. Transitions from classroom to playground and back dropped from 4 min each way to less than 1 min each way. The results of comparing the two schools showed classroom off-task behaviors such as fidgeting and moving around the room decreased significantly, while attentional focus improved significantly as a result of the intervention. LiiNK Project results from grades kindergarten and 1 in the same schools last year are congruent with the results of this study. Next steps will include public school expansion to explore student diversity among rural, urban, and suburban environments with the play and character intervention.